EVALUATION OF LEPTIN IN SERA AND FOLLICULAR FLUIDS OF INFERTILE WOMEN UNDERGOING INTRA-CYTOPLASMIC SPERM INJECTION AND THEIR EFFECTS ON PREGNANCY OUTCOME (Iraqi Journal of Medical Sciences, 2016)
Background: Leptin may serve as the critical link between the body’s adipose tissue and the hypothalamo-pituitary axis, thus it is considered a possible link between nutrition and reproduction.Objective:To evaluate leptin in the serum and follicular fluid and its effect on fertilization rate and pregnancy outcome in infertile female patients undergo intra-cytoplasmic sperm injection cycle.Methods:Seventy four infertile women who agreed to participate in the study were selected randomly from those attending the Fertility Centre in Al-Sader Teaching Hospital, Holly Najaf. Hormonal analysis was done for serum and follicular fluid leptin hormone at the day of ovum pickup.Result: Serum and follicular fluid leptin hormone levels were increased above its normal cutoff level according to the kit used. There was a relationship between the fertilization rate and leptin in serum and follicular fluid. Fertilization rate was significantly (p = 0.049) different depending on the serum leptin level while it has nothing to do with follicular fluid leptin hormone. On the other hand, follicular fluid leptin significantly (p = 0.04) affect pregnancy outcome.Conclusion: Leptin provides possible impact on oocyte and/or embryo quality leading to impaired endometrial bed preparation that may be involved in pregnancy failure.Keywords: Leptin, ferilization rate, pregnancy outcome.